PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI APARATUR DESA INYA DISTRIK MANOKWARI UTARA - Lea Towansiba, Anike; Herin, Theodorus Lamaurin; Torano, Nety (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the effect of leadership style on the employee performance of Desa Inya Village apparatus, North Manokwari District. The research used a quantitative approach with simple linear regression analysis. Data were collected from 30 respondents using a census sampling technique through Likert-scale questionnaires. Results indicate that leadership style has a positive and significant effect on village apparatus employee performance, with a regression coefficient of 0.712, a t-value of 8.437 exceeding the t-table value of 2.048, and a significance value of 0.000. The coefficient of determination (R²) of 0.714 indicates that 71.4% of the variation in village apparatus employee performance can be explained by leadership style, while the remaining 28.6% is influenced by other factors. This research emphasizes the importance of applying democratic, transformational, and participative leadership styles to sustainably improve village apparatus performance.